Malay Apple (Syzygium malaccense) Fruit Calendar: A Case in Central Java - Pudji Widodo; Elly Proklamasiningsih (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
AbstractMalay apple (Syzygium malaccense) is a kind of popular fruit tree originally from Indo-Malayan-Region or South East Asia. There are many environmental factors affecting the flowering time, infrutescence number, fruit size, and fruit number, such as fruit position on the spur, spur size, fruit number set on the spur, and the date of flowering. The objectives of this study were to find out the fruit production during dry and wet seasons, so that fruit calendar can be determined. The method used in this study was survey and observation on Malay apple trees in Banyumas, Purbalingga, and Kebumen from 2018 to 2021. The results of this study showed that June, July, and August when the precipitation was the lowest, the fruit number is the highest, and fruit size is the smallest (145–175 mL). On the other hand, when the precipitation was high (September-April), the fruit was the largest (180–500 mL). Fruit harvest time might change every year depending on climatic factors such as average daily temperature and precipitation. There is no specific harvest time for Malay apples. The implementation of the results of this research is that we do not need to predict when the Malay apple harvest season will be, because the harvest time can be at any time.AbstrakJambu bol (Syzygium malaccense) merupakan salah satu jenis pohon buah-buahan populer yang berasal dari Wilayah Indo-Malayan atau Asia Tenggara. Banyak faktor lingkungan yang memengaruhi waktu berbunga, jumlah bunga, ukuran buah, dan jumlah buah, seperti posisi buah pada tajuk, ukuran tajuk, jumlah buah tiap dompol, dan tanggal berbunga. Penelitian ini bertujuan untuk mengetahui produksi buah pada musim kemarau dan musim hujan, sehingga dapat ditentukan kalender buah. Metode yang digunakan dalam penelitian ini adalah survei dan observasi pada pohon jambu bol di Banyumas, Purbalingga, dan Kebumen dari tahun 2018 sampai dengan tahun 2021. Hasil penelitian ini menunjukkan bahwa pada bulan Juni, Juli, dan Agustus curah hujan paling rendah, jumlah buahnya paling tinggi, dan ukuran atau volume buahnya relatif paling kecil (145–175 mL). Sebaliknya, ketika curah hujan rata-rata tinggi (September-April), buahnya berukuran besar, dengan volume 180–500 mL. Waktu panen buah dapat berubah setiap tahun tergantung pada faktor iklim seperti suhu harian rata-rata dan curah hujan. Hasil penelitian ini menunjukkan bahwa tidak ada waktu yang spesifik untuk waktu panen jambu bol. Implementasi dari hasil penelitian ini adalah bahwa kita tidak perlu memprediksi kapan musim panen jambu bol, karena waktu panen bisa kapan saja.